Professional parallel programming with C♯ : master parallel extensions with .NET 4 - Hillar, Gastón C. (Gastón Carlos) (Wrox professional guides., 2011)
Are you maximizing the processing power in your multi-core computer systems? With this resource, you discover how to do exactly that, while gaining insight into concurrent programming with tasks to create professional parallel applications using C♯ 4, .Net 4, and Visual Studio 2010. You learn other parallel programming techniques, including modern single instruction, multiple data instructions and vectorization. Plus, you explore the possibilities offered by modern parallel libraries and advanced Intel tools with C♯. Use the new lightweight coordination structures to tackle the most complex concurrent programming problems and develop your own customized solutions. --Book Jacket.